Dental care to patients with comorbities in front of the COVID-19 pandemic (Research, Society and Development, 2020)
The COVID-19 pandemic represents the greatest public health challenge in the 21st century, where dental practices represent a risk area, whether due to proximity to the patient or the generation of aerosols in the dental office. In this scenario, patients with comorbidities, which are those who have some disease associated with the other, and who carry them together, can be directly affected by the current situation, since they are highly vulnerable to infection by Sars-CoV-2 and problems with subsequent health conditions. Assistance to these patients requires special care even before the pandemic, which uses technical knowledge and careful evaluation, taking into account the clinical condition of these patients before the dental procedure. With the advent of the COVID-19 pandemic, dental care for these patients has changed the relationship between professional and patient, as well as structural issues in the clinical environment, in order to reduce the risk of contamination. These adjustments need to be discussed, as these patients expect continuous support and individualized risk assessment. Thus, the preparation of the dentist to assist patients with comorbidities during this pandemic period is of fundamental importance, in order to provide the necessary support and recognize the changes that have occurred, making better use of the technological tools, fundamental for contact with the patient. in that context.